Leveling of triggers: a comprehensive summative content analysis of factors contributing to physical violence in emergency medical services - Mohammad Torabi; Ali Afshari; Rasoul Salimi; Afshin Khazaei (BMC Emergency Medicine)
Abstract Background The literature has identified numerous factors that contribute to workplace violence, ranging from environmental stressors to interpersonal conflict. However, a gap remains in our understanding of the specific factors associated with physical violence, particularly concerning its frequency and perceived significance. Methods A summative content analysis was conducted via the electronic survey platform Porsline in Iran for data collection. In April 2024, EMTs working in urban, road, and air bases in western Iran participated in the study. In total, 358 EMTs were selected via convenience sampling. They provided open-ended responses to the following question: “What do you believe are the most significant factors contributing to physical violence in your workplace?” Results The analysis resulted in a comprehensive list of 1,407 descriptions, organized into 20 subcategories and further consolidated into ten main categories. The category with the highest frequency was “legal and policy deficiencies,” with a frequency of 3103, and the category with the lowest frequency was “workplace culture and professional satisfaction,” with 579. The categories based on frequency and significance included “legal and policy deficiencies,” “cultural and societal barriers,” “insufficient training and practical skills,” “shortcomings in organizational safety and support,” “interpersonal and operational pressures,” “organizational culture and workforce dynamics,” “barriers to effective prehospital care,” “resource and infrastructure limitation,” “challenges in interagency coordination and support,” and “workplace culture and professional satisfaction.” Conclusion Legal reforms addressing legal inadequacies, enhancing organizational support systems, and implementing targeted training programs to mitigate conflicts are essential for fostering a safer working environment. By addressing these pressing issues, healthcare facilities can enhance emergency care, safeguard the well-being of emergency responders, and increase the quality of emergency medical services for communities.